Homogeneous Cyclocarbonylation of Alkenols with Iron Pentacarbonyl - Babjak, Matej; Markovič, Martin; Kandríková, Beáta; Gracza, Tibor (Synthesis, 2014)
We report substantially improved reaction conditions for palladium(II)-catalyzed tandem cyclization–intramolecular oxycarbonylation of (amino)polyols with a terminal double bond, based on utilization of iron pentacarbonyl [Fe(CO)5] as an affordable and safe liquid supply of the carbonyl unit fully replacing gaseous carbon monoxide. Direct comparison with the classical version on a series of previously published substrates illustrates invariably shorter reaction times but comparable yields and selectivity.
Keywords: carbonylation; carbonyl complexes; homogeneous catalysis; palladium; iron